Research on Enterprise Data Security Protection Technology on Cloud Platforms - Pan, Yu (European Journal of AI, Computing & Informatics, 2025)
With the popularization of cloud computing technology, enterprises are increasingly relying on cloud platforms for data storage and processing. Although cloud platforms bring flexibility and scalability to enterprises, data security concerns have become increasingly prominent. Due to the openness and resource sharing characteristics of cloud platforms, enterprises face multiple security challenges in data storage, transmission, and access permission management. This article elaborates on the basic definition of data security and provides an in-depth analysis of the data protection management model in cloud computing platforms. It further discusses the technical security challenges in multiple aspects such as data storage, transmission, and identity verification, and introduces various protective measures such as data encryption, data backup, and strengthened access permission management. By adopting these technological solutions, enterprises can effectively defend against the risks of data leakage and unauthorized access, ensuring the confidentiality, integrity, and availability of cloud platform data.